Intersectionality: older adult women - Podestá, Luis Jorge (2022)
This brief legal article analyzes the issues affecting elderly women and develops some solutions that exist to combat them. The analysis of different concepts (vulnerability, intersectionality, among others) is used to arrive at the description of the subject that studies them, a discipline whose object is these subjects in a special situation of vulnerability. Likewise, certain legal rules structuring this topic and specialty are studied and separated, such as the legal institutions and tools (local, national and international), as a solution to these issues. Particularly, we analyze those cases in which elderly women are in a condition of vulnerability, a situation that requires a greater commitment by legal operators to achieve certain procedures (in a broad sense) according to the severity of these cases. Finally, some proposals are offered to achieve the best possible right (optimization mandates) for this group of vulnerable people.